Redefining "dominating" and "contributing" physical factors of indoor thermal comfort in hot-and-humid climate of Malaysia - Maarof, Shafizal; Jones, Phillip (Universiti Putra Malaysia Press, 2019)
In many tropical countries, the cause of the thermal discomfort is mostly due to the presence of high humidity and high air temperature. Air movement, on the other hands, has been considered as the best method in improving the thermal comfort level for this region. Many researches had been conducted regarding the factors affecting thermal comfort for tropical countries and as a result several ideas had been introduced on how the factors affecting the thermal comfort. Most of the research conducted on thermal comfort for tropical countries combined two or more factors as a joint factor such as air temperature and humidity. With the combination of two or more factors (joint factors), the dominant factor among the main factors and how people react to each of these factors especially with the presence of other factors are still in question. The research explore on how people react to each of these three main factors which consequently provides the hierarchy of importance among the three factors. The paper exposes the ‘dominating” factor which is the air temperature that must be presence at all time to affect thermal comfort. The humidity level and air movement are defined as ‘contributing’ factors rather than joint factors in affecting thermal comfort for tropical countries since the presence of both factors can only influence the thermal comfort level depending on the air temperature level.